2009
DOI: 10.1007/s11738-009-0425-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silicon on chilling-induced changes of solutes, antioxidants, and membrane stability in seashore paspalum turfgrass

Abstract: We present a detailed study to investigate if silicon supplementation enhances chilling resistance of seashore paspalum (Paspalum vaginatum Swartz) turf. An enhanced growth status suggests an improved chilling resistance by Si addition, which is coupled with the observation of more Si cells in leaf epidermal cells, as well as a lower LT 50 (the low temperature required to cause 50% electrolyte leakage). Chilling stress induces significant adaptive increases of free proline (P \ 0.01), all soluble sugar (P \ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Liu et al (2009) observed that during low temperature (day/night; 15/8°C), Si applied to hydroponically cultivated cucumber plant were more resistant to chilling stress compared to non-Si application and was attributed to more activated antioxidants such as SOD, GSH, APX, GR, MDHAR, and AsA (Table 1). Almost same tendency of chilling (day/night; 15/5°C) stress tolerance was observed in turf grass as well, after Na 2 SiO 3 fertilization into soil (He et al, 2010; Habibi, 2016; Table 1). …”
Section: Thermal Stresssupporting
confidence: 57%
“…Liu et al (2009) observed that during low temperature (day/night; 15/8°C), Si applied to hydroponically cultivated cucumber plant were more resistant to chilling stress compared to non-Si application and was attributed to more activated antioxidants such as SOD, GSH, APX, GR, MDHAR, and AsA (Table 1). Almost same tendency of chilling (day/night; 15/5°C) stress tolerance was observed in turf grass as well, after Na 2 SiO 3 fertilization into soil (He et al, 2010; Habibi, 2016; Table 1). …”
Section: Thermal Stresssupporting
confidence: 57%
“…In our study, the shape of chloroplasts was improved by Si amendment, and the chloroplast membranes were stabilized. Our results supported previous studies that found that, under cold stress, Si amendment enhanced oxidative defense systems and the chlorophyll content, and reduced the absolute electrolyte leakage quantity of corn plantlets [21,22,58,59]. These results indicate that Si enhances the resistance of plants to cold stress.…”
Section: Discussionsupporting
confidence: 92%
“…Mean values in each bars significantly differ from the control at: *P < 0.05, **P < 0.01, ***P < 0.001 according to Student's test. protection at low temperature (Posmyk and Janas, 2007;He et al, 2010).…”
Section: Resultsmentioning
confidence: 99%